2015
DOI: 10.1017/s1751731115000907
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression during testis development in Duroc boars

Abstract: Androstenone is a steroid pheromone occurring in the pubertal Leydig cells. Breeding against androstenone can decrease pheromone odour in swine meat but appears to cause unwanted side effects such as delayed onset of puberty. To study causality, global gene expression in developing boar testes at 12, 16, 20 and 27 weeks was investigated using a porcine cDNA microarray. The morphological status and androgenic levels of the same individuals have been described in a previous publication. In the present paper, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Estrogen concentrations have been found to be correlated with androstenone in adipose tissue 90 , 91 . The roles of the MAPK pathway in variation of BT has recently been shown in a gene expression study on Duroc boars 92 . The authors found that upregulation of MAPK coincided with pubertal increase in androstenone and testosterone production 92 as the upregulation was observed several weeks earlier than complex morphological restructuring of testis into reproductive tissue.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Estrogen concentrations have been found to be correlated with androstenone in adipose tissue 90 , 91 . The roles of the MAPK pathway in variation of BT has recently been shown in a gene expression study on Duroc boars 92 . The authors found that upregulation of MAPK coincided with pubertal increase in androstenone and testosterone production 92 as the upregulation was observed several weeks earlier than complex morphological restructuring of testis into reproductive tissue.…”
Section: Discussionmentioning
confidence: 96%
“…The roles of the MAPK pathway in variation of BT has recently been shown in a gene expression study on Duroc boars 92 . The authors found that upregulation of MAPK coincided with pubertal increase in androstenone and testosterone production 92 as the upregulation was observed several weeks earlier than complex morphological restructuring of testis into reproductive tissue. Furthermore, proteins encoded by MAPK may regulate the Steroidogenic Acute Regulatory protein (STAR) (a cholesterol traffic regulator) and have a complex interaction with steroidgenesis (see review by Manna and Stocco 93 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Only few studies have attempted to use a microarray as a tool to study global transcriptome analysis in testis development and sperm maturation in different species. Lervik et al [15] evaluated the developmental changes in boar testes from 12 to 27 weeks, and found that transcripts regulating steroidogenesis act at specific developmental stages. Another study identified genes with crucial roles in sperm formation, maturation and fertility, which have similar regulation across various species [16].…”
Section: Discussionmentioning
confidence: 99%